UJI TOKSISITAS KITOSAN CANGKANG KERANG BULU (Anadara antiquata) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Nadila Indra Sepvina; Ridwanto Ridwanto; Zulmai Rani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Shellfish is one of Indonesia's fishery commodities which is increasing every year, one of which is blood clams and feather shells, which are easily found in Southeast Asia and East Asia. Shellfish also have great potential so that it has an impact on the increasing waste that is allowed to accumulate without any handling of the pollution that exists in the environment and society. One alternative to the use of waste from feather shells to have a high use value is to isolate it into chitosan. The purpose of this study was to investigate the utilization of shellfish waste into chitosan and to determine the LC50 value of the chitosan produced. The analysis carried out was the toxicity test of chitosan from shellfish shell waste on Artemia salina Leach shrimp larvae using the Brine Shrimp Lethalitiy Test (BSLT) method with various concentrations of 100; 250; 500; 750; and 1000 µg/mL, and determining the value of LC50 by probit analysis. Based on the results of the toxicity test of chitosan from shellfish waste, the LC50 value was µg/mL. These results indicate that chitosan from shellfish waste has no toxic effect on Artemia salina Leach shrimp larvae.